PELAKSANAAN PROGRAM UPAYA PENINGKATAN PENDAPATAN KELUARGA (UP2K) DI DESA SUNGAI TOHOR KEC.TEBINGTINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - ", Maryati; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Existing programs in shallow river are programs UP2K, Programs UP2K is one form of programs taken by the government that is focused on women and only priority to those who are less able or minimal capital to start or expand their business, so they are not able to increase and resulted in income of those unable to support the domestic economy.The concept of the theory used is the theory that Management Implementation according to Terry, in Manullang which states that the implementation of management functions or mover is the most important and dominant in the management process. So, we need leadership, motivation and communication in practice. These factors are the Human Resources (HR), Technology and Management.This study aims to determine how the implementation and the factors that affect the implementation of the Program to Increase Family Income (UP2K) in Sungai Tohor district. East High Cliff Meranti Islands District. Researchers used a qualitative descriptive approach using purposive sampling method with data collection using interviews, observation, and documentation.The result of this research is the implementation of the Program to Increase Family Income (UP2K) in shallow river district. East High Cliff Meranti Islands District. Factors that affect, among others: Human Resources (HR), Technology and Management.Keywords: Management, Implementation, and Programs UP2K.